922 views
4 votes
F(x)=3x^3-12x^2+9x what the factor


User Grenzbotin
by
4.8k points

2 Answers

1 vote

Answer:

3x(x - 1)(x - 3)

Explanation:

the sum of the coefficients = 3 - 12 + 9 = 0

hence x = 1 is a root of f(x) and (x - 1) is a factor

dividing 3x³ - 12x² + 9x gives

f(x) = (x - 1)(3x² - 9x)

= (x - 1)3x(x - 3) = 3x(x - 1)(x - 3) ← in factored form

User Palimondo
by
5.6k points
2 votes

Answer:

f(x) = 3x(x-1)(x-3)

Explanation:

f(x) = 3x³-12x²+9x = 3x(x²-4x+3) =

= 3x(x²-x-3x+3) = 3x[x(x-1)-3(x-1)] =

= 3x[(x-1)(x-3)] = 3x(x-1)(x-3)

User Waves
by
5.8k points